CARL FREDRICKSEN'S STRUGGLE FOR MAKING DREAM COME TRUE IN PETE DOCTER'S UP MOVIE (2009): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - HARSIWI, TUTI (2011)
The major problem of this study is how struggle of Carl Fredricksen reflected in the major character's personality. The objective of the study is to analyze the movie based on structural elements and to analyze struggle for making dream come true of Carl Fredricksen based on an individual psychological approach. This study focuses on the major character, namely Carl. The benefit of this study is to give additional information which can be used by the other literature researchers who are interested in analyzing this play. This study uses two data sources, namely primary and secondary data source. The primary data source is the movie itself, Up by Pete Docter, while the secondary data taken from some information needed. The method of data collection is qualitative method. Based on the analysis, the writer concludes that struggle for making dream come true of Carl Fredricksen is influenced by some aspects. Carl has goal to find the Paradise Falls as his wife's dream. He has to control his inferiority feeling that he can't fulfill his wife's dream. He is striving for superiority, he has avoiding type, low social interest and he has creative power. Based on An Individual Psychological aspects shown in the film, the writer then concludes that literary work reflects the condition of people who has a dream or goal and they struggle to get it.